Effect of Y content on hot tearing susceptibility of MgZn9YxZr0.5 alloys - JIA Dong-rui; WANG Yue; LIU Zheng; MAO Ping-li; WANG Feng; WANG Zhi (Cailiao gongcheng, 2019)
Based on the Clyne-Davies model,the hot tearing susceptibility(CSC)of MgZn9YxZr0.5(x=1,2,4,6,mass fraction/%) was predicted.The microstructure and morphology of hot tearing regions of the alloys were observed by X-ray diffraction (XRD) and scanning electron microscopy (SEM) and the curves of solidification shrinkage stress with temperature (or time) of MgZn9YxZr0.5 alloys based on the "T" type hot tearing permanent-mold were collected.The results demonstrate that the predicted values of CSC are consistent with that of measured values of crack volume.The hot tearing susceptibility of the alloys from high to low is:MgZn9Y1Zr0.5 > MgZn9Y6Zr0.5 > MgZn9Y2Zr0.5 > MgZn9Y4Zr0.5;the dendrite coherency temperature and the initial temperature of hot tearing decrease with the Y content increasing when w(Y) is not more than 4%.When w(Y) is 6%, the dendrite coherency temperature and the initial temperature of hot tearing increase.With the increase of Y content, the change of precipitation phase type, content and the dendrite tendency of α-Mg in the solidification process of MgZn9YxZr0.5 alloys is considered as the main micro-mechanism that affects crack initiation,propagation and hot tearing in grain boundary.